Experience in the use of chemical bleaching gel based on 40% hydrogen peroxide in patients with acquired discolorite (LLC "Endo Press", 2020)
For most people regular brushing is a habit, that is forming usually from one to three months and is maintained by motivation, the stimulation of which largely depends on the information environment. Сlinical judgment of efficiency and safety of chemical bleaching were evaluated in real work with group of patients up to 25 years with acquired dental discoloration. The experiment had shown that the use of the gel with 40% hydrogen peroxide is safe and effective (8-10 shades according to VITA scale) system for teeth whitening, without using expensive lamps and additional equipment.